2018
DOI: 10.1002/jpen.1178
|View full text |Cite
|
Sign up to set email alerts
|

High‐Dose Human Milk Feedings Decrease Oxidative Stress in Premature Infant

Abstract: Our results demonstrate that predominantly HM feedings were associated with decreased oxidative stress, whereas PF feedings increased oxidative stress in premature infants, even after controlling for perinatal oxidant exposures of HMF or PF introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…Taking together these characteristics, feeding with PIF2 rather than PIF1 would seem to result in a lower oxidative load for the preterm newborn, although the best choice is always human milk, irrespective of pasteurization. These data confirm those found by other authors by in vivo studies [40,41,42,43,44], who reported higher excretion of oxidised compounds in infants consuming infant formulas, with respect to human milk.…”
Section: Resultssupporting
confidence: 92%
“…Taking together these characteristics, feeding with PIF2 rather than PIF1 would seem to result in a lower oxidative load for the preterm newborn, although the best choice is always human milk, irrespective of pasteurization. These data confirm those found by other authors by in vivo studies [40,41,42,43,44], who reported higher excretion of oxidised compounds in infants consuming infant formulas, with respect to human milk.…”
Section: Resultssupporting
confidence: 92%
“…BM antioxidants are important, particularly in the context of prematurity, due to the susceptibility of these infants to oxidative stress. Urinary excretion of hydroxy-deoxyguanosine, a marker of DNA oxidative damage, is lower in BM fed infants compared to those fed with formula [29,30]. Similar results have been found measuring urinary F2-isoprostane [30] or MDA [31], stable biomarkers of oxidative damage to lipids.…”
Section: Discussionsupporting
confidence: 72%
“…Urinary excretion of hydroxy-deoxyguanosine, a marker of DNA oxidative damage, is lower in BM fed infants compared to those fed with formula [29,30]. Similar results have been found measuring urinary F2-isoprostane [30] or MDA [31], stable biomarkers of oxidative damage to lipids. Moreover, feeding with BM is associated with a lower incidence of a variety of oxidative-stress related illnesses in premature infants [14].…”
Section: Discussionsupporting
confidence: 72%
“…The breast milk has the status of a gold standard food and it is recommended by the scientific community (AAP, ESPGHAN) and not only (WHO/ UNICEF) as the first choice for premature infants. This is linked to the numerous benefits of feeding with breast milk, starting from the reduced risk of NEC, sepsis, other comorbidities [1835] (ROP, BPD), a better enteral tolerance with a faster achievement of the full diet [33], as well as positive effects on neurocognitive and behavioral development, long-term visual acuity, and a reduction of the risk of metabolic and degenerative diseases during the adolescence and the adulthood [916]. All this is attributable to the countless biocomponents present in the breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the scientific societies and the organizations that deal with health, indicate the mother's milk as the first choice; otherwise, whether the mother's milk was not available, one should refer to the donated milk. Although the evidences on the protective effect of the donated milk on the pathologies related to the premature birth are not so overwhelming, the only clearly demonstrated evidence is on the NEC, the data available, and the experience of the centers that dispose milk banks evoking the conservation of the majority of the beneficial effects of human milk [2735], within the framework of the treatment methods of the human milk. Furthermore, the presence in NICU of a HMB acts as a facilitator for the nursing of term and preterm infants [36].…”
Section: Introductionmentioning
confidence: 99%